2006
DOI: 10.4103/0378-6323.29334
|View full text |Cite
|
Sign up to set email alerts
|

Prurigo pigmentosa: An underdiagnosed disease?

Abstract: Prurigo pigmentosa is a distinctive inflammatory disease first described by the Japanese dermatologist Masaji Nagashima in 1971. It is typified by recurrent, pruritic erythematous macules, papules and papulovesicles that resolve leaving behind netlike pigmentation. The disease is rarely diagnosed outside Japan, because clinicians outside Japan are not well conversant with the criteria for its diagnosis. Only one patient from India has been published previously under the diagnosis of prurigo pigmentosa, a hint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(83 citation statements)
references
References 0 publications
0
80
0
3
Order By: Relevance
“…2,6,8 However, in our study, emotional stress was the only aggravating factor reported. It has been speculated that PP is, in fact, not triggered by dietary changes, 12 perhaps explaining why its symptoms appear to be recurrent and exacerbated by unknown factors in most of our patients. PP has been treated by doxycycline, minocycline and dapsone to good effect 1,2,6,8 ; minocycline appears to be more effective than doxycycline and dapsone due to its rapid resolution and fewer adverse side-effects in treating PP.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,8 However, in our study, emotional stress was the only aggravating factor reported. It has been speculated that PP is, in fact, not triggered by dietary changes, 12 perhaps explaining why its symptoms appear to be recurrent and exacerbated by unknown factors in most of our patients. PP has been treated by doxycycline, minocycline and dapsone to good effect 1,2,6,8 ; minocycline appears to be more effective than doxycycline and dapsone due to its rapid resolution and fewer adverse side-effects in treating PP.…”
Section: Discussionmentioning
confidence: 99%
“…İnflamatuar fazda kaşıntılı, eritemli maküler, papüler, papüloveziküler lezyonlar; rezolüsyon fazında ise retiküler pigmentasyon izlenmektedir. 2,6 PP'nin histopatolojik özellikleri karakteristik olmamakla birlikte, PP tanısının konulmasında yardımcı olmaktadır. Böer ve ark.…”
Section: Resi̇m 3: Gövde Posterior Alt Kısmında Orta Hatta Retiküler Tunclassified
“…brown to gray-brown patches on the face melasma [45,53], dark plaques on skin, (post inflammatory hyper pigmentation) [53][54][55], light to dark brown spots of 1 to 20 cm ("Café-au-lait" macules) [53], pale brown to dark brown spots on the skin (agespots or solar lentigo) [53], well-circumscribed round to oval or irregular grey patches on the face, neck and trunk (Erythema dyschromicum perstans), netlike pigmentation (Prurigo pigmentosa) [56,57], dark vertical line across the abdomen in pregnant females (linea nigra) [58].…”
Section: Hyperpigmentation Disordersmentioning
confidence: 99%